Replication of Heterochromatin and Structure of Polytene Chromosomes - Leach, Thomas J. (American Society for Microbiology, 2000)
Heterochromatin is characteristically the last portion of the genome to be replicated. In polytene cells, heterochromatic sequences are underreplicated because S phase ends before replication of heterochromatin is completed. Truncated heterochromatic DNAs have been identified in polytene cells of Drosophila and may be the discontinuous molecules that form between fully replicated euchromatic and underreplicated heterochromatic regions of the chromosome. In this report, we characterize the temporal pattern of heterochromatic DNA truncation during development of polytene cells. Underreplication occurred during the first polytene S phase, yet DNA truncation, which was found within heterochromatic sequences of all four Drosophila chromosomes, did not occur until the second polytene S phase. DNA truncation was correlated with underreplication, since increasing the replication of satellite sequences with the cycE(1672) mutation caused decreased production of truncated DNAs. Finally, truncation of heterochromatic DNAs was neither quantitatively nor qualitatively affected by modifiers of position effect variegation including the Y chromosome, Su(var)205(2), parental origin, or temperature. We propose that heterochromatic satellite sequences present a barrier to DNA replication and that replication forks that transiently stall at such barriers in late S phase of diploid cells are left unresolved in the shortened S phase of polytene cells. DNA truncation then occurs in the second polytene S phase, when new replication forks extend to the position of forks left unresolved in the first polytene S phase.